2018
DOI: 10.3855/jidc.10128
|View full text |Cite
|
Sign up to set email alerts
|

Stethoscope, “the friendly foe” – A study to evaluate bacterial contamination of stethoscopes and disinfection practices

Abstract: Introduction: Stethoscope is used to assess the health of patients but can also act as a potential source of disease transmission. The study was aimed to find out the contamination rate of stethoscopes, evaluate awareness and attitude of healthcare workers (HCWs) about stethoscope cleaning, and determine the efficacy of 70% alcohol as cleaning agent. Methodology: This hospital based cross-sectional study was conducted in a tertiary care hospital in October 2015 among healthcare workers. They were asked t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
19
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 14 publications
6
19
1
2
Order By: Relevance
“…Moreover, 70 studies were commentaries or full articles not in line with the aim of the study and we have excluded them after a careful examination of the abstracts and of the full texts. Finally, we detected 17 publications [3,5,6,9,11,13,[17][18][19][20][21][22][23][24][25][26][27]. Among these, we included four letters to the editor (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, 70 studies were commentaries or full articles not in line with the aim of the study and we have excluded them after a careful examination of the abstracts and of the full texts. Finally, we detected 17 publications [3,5,6,9,11,13,[17][18][19][20][21][22][23][24][25][26][27]. Among these, we included four letters to the editor (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Datta et al [27] proved that IPA is significantly effective in disinfection. A total of 100 stethoscope diaphragms were analyzed before and after cleaning with IPA.…”
Section: Resultsmentioning
confidence: 99%
“…Günlük tıbbi uygulamada en sık kullanılan araçlardan biri olan stetoskop, oldukça fazla sayıda hastayla temas ettiği için sık sık kirlenmektedir. Bu tür tıbbi cihazlar, düzenli olarak temizlenmezse infeksiyon kaynağı haline gelebilirler [16] . Datta ve arkadaşları sağlık çalışanları arasında stetoskop temizliğine verilen önemi araştırdıkları çalışmada hemşirelerin doktorlara kıyasla stetoskoplarını daha sık temizlediklerini ve bu bulguya paralel olarak doktorlara ait stetoskoplarda daha fazla bakteriyel kolonizasyon olduğunu saptamışlardır [16] .…”
Section: Discussionunclassified
“…Bu tür tıbbi cihazlar, düzenli olarak temizlenmezse infeksiyon kaynağı haline gelebilirler [16] . Datta ve arkadaşları sağlık çalışanları arasında stetoskop temizliğine verilen önemi araştırdıkları çalışmada hemşirelerin doktorlara kıyasla stetoskoplarını daha sık temizlediklerini ve bu bulguya paralel olarak doktorlara ait stetoskoplarda daha fazla bakteriyel kolonizasyon olduğunu saptamışlardır [16] . Yapılan başka bir çalışmada da hemşirelerin doktorlara kıyasla stetoskoplarını daha sık temizledikleri ve hemşirelere ait stetoskopların daha az kolonize olduğu bildirilmiştir [15] .…”
Section: Discussionunclassified
“…5,14,16,18 The bacterial diversity of stethoscopes and other noncritical devices has been examined in depth, and the results reveal that they can be used to disseminate microorganisms. 14,[19][20][21][22][23][24][25][26][27][28] The findings of these studies and others have revealed a wide range of contamination rates ranging between 30-100%, as well as a variety of bacteria. 21,23,[29][30][31][32] These bacteria include the following Streptococcus, Porphyromonas, Escherichia coli, Corynebacterium, Methicillin-sensitive, and methicillinresistant Staphylococcus aureus (MRSA), Pseudomonas aeruginosa, Granulicatella, Propionibacterium, Bacteroides, Prevotella, vancomycin-resistant Enterococcus (VRE), and Clostridium difficile, etc.…”
mentioning
confidence: 99%